Implementation of a Polycrystalline PV-Based PJU System to Support Mobility and Psychological Environmental Safety in Gondosuli Village - Aryudho Widyatno; Fuad Indra Kusuma; Sucipto; Moh. Zainul Falah; Wahyu Tri Handoko; Farah Wardatul Afifah; Sujito (CV. Creative Tugu Pena, 2024)
Public street lighting (PJU) is critical because it affects the safety and security of road users, particularly at night when appropriate lighting is required. Inadequate street illumination can be harmful to society, increasing the likelihood of accidents and street crime. Mr. Muhammad, the Head of Gondosuli Village in the Pakuniran district, underlines the need for public street lighting. In this context, public street lighting is particularly required for activities in the region at night, so that it can encourage tourism, security, accessibility, and increase community welfare because the existing street lighting in Gondosuli is very inadequate. As a result, these partners considered the development of public street lighting (PJU) as a critical necessity in the region. Polycrystalline photovoltaics (PV) are a form of solar cell that generates electricity from sunlight. Polycrystalline PV is made from a semiconductor material like silicon that has been manufactured into tiny wafers with crystals aligned in diverse directions. Solar Photovoltaic Power Generation (PLTS) systems utilize polycrystalline photovoltaics (polycrystalline PV).